Psychotherapy of Borderline Mental Disorders in Sanatorium-Resort Conditions. Literature Review - Anna A. Kuzyukova; Andrey P. Rachin (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
Psychotherapeutic methods acceptable for sanatoriums were analyzed in this work due to the high frequency of borderline mentaldisorders exampled in the general medical practice, including sanatorium-resort institutions, and the frequent prioritizationof psychotherapy (compared to psychopharmacology) for the treatment of such conditions; as well as the lack of structure in thesystematics of psychotherapeutic methods used in the sanatorium treatment conditions, and the frequent lack of convincing evidenceof their effectiveness. Aim. Various group and individual methods that can be used for short-term psychotherapy have been studied. In accordance with the modern principles of evidence-based medicine, an assessment of the available evidence of their effectiveness was carried out. Material and Methods. The RSCI and Medline electronic databases were used, the search was carried out by keywords (names of relevant techniques and mental dysfunctions, such as anxiety, depression, adjustment disorders, stress states, psychosomatics). The efficacy and safety evidence levels were evaluated in accordance with the National Standard of the Russian Federation GOST R 56034-2014. Results. As a result of the work performed, a wide range of psychotherapy methods related to its various directions, applicable in sanatorium-resort conditions (most of them are also suitable for hospitals/rehabilitation centers) is analyzed. Some of them have a high level of evidence, while others have less convincing data, which is often associated with the difficulty of reproducing them in experimental conditions. Conclusion. The information provided may be useful to specialists working in sanatoriums, rehabilitation centers and hospitals, for solving issues of organizing and improving the quality of psychotherapeutic care for patients with concomitant borderline mental disorders as well as for further scientific research.